A New Record of Nebuchadrezzar’s Palestinian Campaigns - Malamat, A.
The Chronicle of the Years 608-606 — The Chronicle of the Years 605-595 — The Conquest of Ashkelon and the Fast of Judah — The Conquest of Jerusalem and the Exile of Jehojahu — The Oracles of Jeremiah.